Answer:
-9
Step-by-step explanation:
5 - 14 = -9
-9 + 0 = -9
Answer:
![{x}^{2} - 18x - 21](https://tex.z-dn.net/?f=%20%7Bx%7D%5E%7B2%7D%20%20-%2018x%20-%2021)
Step-by-step explanation:
![{x}^{2} + 3 - 6(3x + 4)](https://tex.z-dn.net/?f=%20%7Bx%7D%5E%7B2%7D%20%20%2B%203%20-%206%283x%20%2B%204%29)
![{x}^{2} + 3 - 18x - 24](https://tex.z-dn.net/?f=%20%7Bx%7D%5E%7B2%7D%20%20%2B%203%20-%2018x%20-%2024)
![{x}^{2} - 21 - 18x](https://tex.z-dn.net/?f=%20%7Bx%7D%5E%7B2%7D%20%20-%2021%20-%2018x)
![\boxed{\green{= {x}^{2} - 18x - 21}}](https://tex.z-dn.net/?f=%20%5Cboxed%7B%5Cgreen%7B%3D%20%20%7Bx%7D%5E%7B2%7D%20%20-%2018x%20-%2021%7D%7D)
3(5j+2)=2(3j-6) do distributed to remove parenthesis 15j+6=6j-3 . Then move all j to left side and the second term to right side 15j-6j=-3-6. Now solve both sides 9j= -9. Now divide both sides by 9 to get j alone to j = -1
Answer:
just add them and leave it as a positive
Step-by-step explanation:
Answer:
m = 2, n = - 3
Step-by-step explanation:
Given the 2 equations
2m + 3n = - 5 → (1)
5m + 3n = 1 → (2)
Subtract (2) from (1) term by term to eliminate n
2m - 5m = - 5 - 1
- 3m = - 6 ( divide both sides by - 3 )
m = 2
Substitute m = 2 into either of the 2 equations and solve for n
Substituting into (1)
2(2) + 3n = - 5
4 + 3n = - 5 ( subtract 4 from both sides )
3n = - 9 ( divide both sides by 3 )
n = - 3